Psychotropic polypharmacy among elderly patients with mental illness in a Malaysian university hospital : a 10-year review of hospital databases - Woon, Luke Sy-Cherng; Gan, LLY (Pusat Perubatan Universiti Kebangsaan Malaysia, 2021)
Psychotropic polypharmacy among elderly patients is problematic due to their multiple comorbidities. This study investigated psychotropic polypharmacy among elderly patients discharged from a Malaysian university hospital and its associated factors. Discharges of patients aged 65 years or above from the psychiatric wards from 2010 to 2019 were reviewed. Sociodemographic data, length of stay (LOS), psychiatric and other diagnoses, and psychotropic prescription upon discharge were extracted from electronic databases. Multiple logistic regression was conducted with age, gender, race, marital status, main psychiatric diagnosis, LOS, and the number of medical comorbidities as independent variables, and polypharmacy (>2 psychotropics) as the dependent variable. There were 354 discharges in this period. The mean age was 72.4 years (SD=5.9 years); 63.0% were female and 39.8% were Malays. Most were married (84.2%). The commonest category of psychiatric diagnosis was mood disorders (54.5%). A total of 76.8% of the discharges involved one or more medical comorbidities. The median number of psychotropics was two, with 38.1% prescribed three or more psychotropics. In the multiple regression model, female gender, Malay race, and being married were significantly associated with psychotropic polypharmacy. Sociocultural factors may contribute to psychotropic polypharmacy among elderly patients. Such factors require further investigations to elucidate their roles.